Рerisinusoidal-centrolobular liver fibrosis: features of morphogenegis and parameters of progression - Tumanskiy, V.A.; Shebeko, Yu.A. (Pathologia, 2013)
The research of morphogenesis of liver fibrosis in 589 patients with chronic viral hepatitis, alcoholic and non-alcoholic steatohepatitis has shown that perisinusoidal-centrоlobular liver fibrosis can develop at chronic liver diseases. This type of liver fibrosis is characterized by collagen deposition and fibrosis in perisinusoidal space of Disse in 3rd-2nd zones of liver acinus and around centrolobular veins at minimal or absent portal fibrosis. Severe perisinusoidal-central-lobular liver fibrosis is manifested by symptoms of portal hypertention before cirrhosis development.